Manipulability analysis of two-arm robotic systems - Ferreira, N. M. Fonseca (2019)
Many tasks involving manipulation require cooperation between robots. Meanwhile, it is necessary to determinate the adequate values for the robot parametrs to obtain a good performance. This paper discusses several aspects related with the manipulability of two co-operative roborts when handling objects with different lenghts and orientations. In this line of thought, a numerical tool is developed for the calculation and the graphical visualizations of the manipulability measure.